Boutique advisory in Europe: acquirers´ choice and performance - Gomes, João Diogo Andrade (2017)
This study analyses how European acquirers determine their choices between boutiques and full-service advisors, and how such choice impacts their announcement returns on M&A transactions. The only study on the impacts from boutiques expertize and independence was performed by Song et al. in 2013, in a US setting. This study attempts to fill a gap in the literature to what regards the value of boutiques in Europe, by focusing on acquirer side only but including both public and private acquisitions, for the period 2000 to 2016. Using a probit model for the determinants in the choice of an advisor, this study’ findings suggest that boutiques expertize and independence are greatly valued in more complex transactions and for acquirers with an inferior need for the funding capacity and reputation of full-service advisors. Yet, some results differ according to target’s status. Finally, using a 2SLS procedure to determine the impacts on acquirers’ returns, the results propose that the European market does not significantly react to the choice of a boutique advisor.